Utilization of 1-(3-aminopropyl)-imidazole in development of pH-sensitive nanocarrier for anticancer drug delivery - Patihul Husni Husni; Norisca Aliza Putriana (Indonesian Journal of Pharmaceutics, 2022)
pH-sensitive nanocarriers have demonstrated as successful drug carriers due to the higher drug accumulation at the tumor site by pH dependent release at acidic tumor microenvironment. Imidazole can be utilized to obtain the pH-sensitive nanocarriers. One of imidazole-based compounds used by researchers in development of pH-responsive carriers is 1-(3-Aminopropyl)-imidazole. This review is focused on utilization of 1-(3-aminopropyl)-imidazole to develop pH-sensitive nanocarrier especially for delivery of anticancer drug. In addition, this review also shows research performed by researchers to develop pH-sensitive nanocarrier for anticancer drug delivery using 1-(3-aminopropyl)-imidazole to prepare imidazole-based pH-sensitive nanocarriers. The data were collected from published journals with 15 and 20 journals as primary and supporting literatures, respectively. Properties of imidazole groups to deprotonate at pH 7.4 and protonate at pH ≤ 6.5 implies that the drug release was pH-dependent, leading to limited release of drug from carriers under physiological pH conditions and diminishing the drug’s effect in blood circulation before reaching the tumor site, resulting in more effective anticancer activity.